The Interaction between Project-Based Learning Models and Learning Creativity on Elementary School Students' Poetry Writing Skills - Azizah Fauzana, Umi; Slamet, St Y; Adi, Fadhil Purnama (International Journal of Elementary Education, 2025)
The poetry writing ability of elementary students remains relatively low in structure, diction, and poetic expression. This condition indicates that conventional learning approaches have not provided sufficient space for creative exploration and expressive development. This gap highlights the need for a contextual, participatory, and creativity-oriented learning model. This study aims to analyze the interaction effect between the Project-Based Learning model and learning creativity on students' poetry writing skills. The research employed a 2x2 factorial quasi-experimental design, involving two groups: the experimental group received project-based instruction, while the control group followed conventional learning. Data were collected through a poetry writing test and a creativity questionnaire. The population in this study were all grade VI students elementary school. The sample selection used cluster random sampling so that two schools were selected as samples, namely the experimental class with 26 students and the control class with 23 students. Data collection was carried out through a poetry writing skills test and a learning creativity questionnaire. The results of the t-test showed a significant difference between the experimental and control groups with a higher difference in score increase in the PjBL group. The results of the N-Gain calculation showed that the experimental group reached the medium category, while the control group was in the low category. The results of the two-way ANOVA test showed that the learning model, learning creativity, and the interaction of the two had a significant influence on poetry writing skills.